Spatial distribution of frontal faults in Nepal Himalaya - Dhital, MR (Journal of Nepal Geological Society, 2008)
Conventionally it has been believed that the Main Frontal Thurst (MFT) and Main Boundary Thrust (MBT) continue throughout the Nepal Himalaya as two continues and subparallel faults. However, detailed field studies, the study of available geological maps, and the analysis of satellite images as well as SRTM data clearly indicate that the situation is more complex. The imbricate frontal faults in the Nepal Himalaya are generally sub-parallel; they trend from NW to SE and extend for tens of kilometres. Each of the faults in this fault swarm terminates in either a fold or another fault. In the latter case, frequently the fault towards the foreland terminates in the fault extending from the hinterland. The Lesser Himalayan and Siwalik rocks constitute imbricate slices and duplexes. Consequently, there are outliers of the Lesser Himalayan rocks in the Siwaliks of east Nepal in the vicinity of Katari, Bagpati, and Kampughat. Hence, the definition that the MBT separates the Lesser Himalayan and Siwalik rocks becomes invalid. A closer look at the Siwaliks reveals that there are a number of independent and discontinues faults at the foreland front. They too cannot be classified as a single fault. Generally, about 20 to 30 km long tight folds extend from the fault tips and there are extensive areas where the Siwalik rocks are overturned. There are also a number of backthrusts in the Siwaliks as well as in the Lesser Himalaya. A normal fault runs very close to the ‘MBT’ between the Mahakali River and Budar as well as in the area between Surkhet and Dang. Steeply inclined Recent gravel beds are observed in the Siwaliks of the Mahakali area in far-west Nepal and at Barphalyang in the Ilam district of east Nepal. Such features clearly indicate that the entire Himalayan frontal fault system is tectonically active. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.2